America's first climate change refugees: Victimization, distancing, and disempowerment in journalistic storytelling. (September 2017) - Herrmann, Victoria
Abstract: The article to follow aims to delve deeper into the underexplored but critical role visual representations play in constructing a public narrative of climate change relocation in the United States. Through a visual discourse analysis of American news sources that portray 'America's first climate change refugees, ' the article explores how media outlets are using images to construct perceptions of meaning, purpose, and power in stories of climate relocation. It argues that journalistic storytelling of sea level rise and relocation has employed a formula of crisis, 'othering, ' and victimization in representing the nexus of environmental change and culture in communities across the United States. Through this, the article shows that images and aesthetic codes have constructed and conditioned perceptions of agency in America's climate discourse that distance and disempower at-risk coastal communities from the reader.